Biosafety evaluation and characterization of occupational risks in a ready care unit paulista, Brazil (Research, Society and Development, 2020)
Health professionals are commonly exposed to risks associated with their craft; however, although their health is guaranteed by the Organic Health Law, there are several times if inappropriate, inefficient or neglected biosafety behaviors are observed. This article aimed to evaluate the facilities and working conditions of employees in a emergency unit, to identify the main occupational risks and to assist the perception of the competent bodies in the identification and reduction of risks of health promoting institutions. Through forms prepared from NR 32, the 112 employees of a emergency unit in the state of São Paulo were evaluated. The study was conducted with 82/112 (73.21%) of employees, with the distribution of positions among nursing technicians (70.7%), nurses (14.6%), and x-ray technicians (6, 1%) pharmacy technicians (4.9) and radiologists (3.7%). Structural disabilities in some sectors were identified during the evaluation, physical constraints compared to the number of attendances, restrictions on material collection and structural maintenance planning, as well as lack of staff preparation for some functions such as the use of fire extinguishers, or negligence regarding the use of personal protective equipment and deficiencies in sanitary protocols. Biosafety actions can prevent and reduce the risks associated with their craft, while also ensuring population and environmental health. This study can serve to guide projects and institutional protocols, with the purpose of reducing risks inherent to professionals and patients of health facilities.